Air pollution might contribute to antimicrobial resistance: a One Health perspective - Leshan Xiu; Shuangqing Hu (Science in One Health, 2025)
Air pollution and antimicrobial resistance (AMR) are two critical challenges that threaten global health and sustainability. Emerging research suggests a significant connection between these phenomena, with air pollution potentially acting as a driver for the development, dissemination, and persistence of antimicrobial resistance genes (ARGs). Drawing on evidence from recent studies, we highlight the mechanisms through which air pollution contributes to AMR, including the role of particulate matter, atmospheric transport, and co-selection pressure. We advocate for a comprehensive One Health approach to address the intertwined threats of air pollution and AMR, emphasizing the need for integrated policies, surveillance, and interdisciplinary research.